Long-term therapy with intravenous zoledronate increases the number of nonattached osteoclasts - Nagata, Maria José H. [UNESP]; Messora, Michel R.; Antoniali, Cristina [UNESP]; Fucini, Stephen E. [UNESP]; de Campos, Natália [UNESP]; Pola, Natália M.; Santinoni, Carolina S.; Furlaneto, Flávia A.C.; Ervolino, Edilson [UNESP] (Elsevier, 2017)
The purpose of this study was to investigate the influence of long-term therapy with intravenous zoledronate (ZA) on the healing of extraction sockets in rats. Forty rats, divided into groups C (Control) and Z (Zoledronate), received intravenous injections of either saline solution or ZA for 24 weeks. Their right maxillary incisor was extracted. Euthanasia was performed at 7 or 28 days postoperative. Histomorphometric (Newly Formed Bone Area) and immunohistochemical (RANKL, OPG and TRAP) analyses were performed. Data were statistically analyzed (ANOVA, Tukey's test and Kruskal–Wallis, Dunn's Multiple Comparison test).Groups C and Z showed similar new bone area, RANKL and OPG immunolabeling. The number of TRAP-positive multinucleated cells was significantly higher in Group Z than in Group C at 28 days. A significantly higher proportion of nonattached osteoclasts were seen in Group Z than in Group C at both periods of analysis. Long-term therapy with intravenous ZA stimulated nonattached osteoclast formation in extraction sockets in rats, thus decreasing local bone resorption. However, it did not influence bone formation by osteoblasts.
Keywords: Bone regeneration; Tooth extraction; Zoledronic acid